Human Capital Constrains in the implemetation of Pesantren Accounting Guidelines (PAP): Evidence from a modern Pesantren Al-Istiqamah Ngata Baru in Central Sulawesi - Arnianti; Suwedy; Nur Rizkianti Suryanto; Muhammad Bashri Bas (Jurnal Sinar Manajemen, 2025)
This study aims to analyze the human resource (HR) constraints in the implementation of the Pesantren Accounting Guidelines (PAP) at Pondok Pesantren Modern (PPM) Al-Istiqamah Ngata Baru, Central Sulawesi. Using a qualitative case study design, data were collected through in-depth interviews, direct observation, and analysis of the pesantren’s financial documents. The findings reveal that limited accounting competencies among staff, lack of PAP socialization and training, absence of professional accountant assistance, and multiple work responsibilities are the main barriers to implementation. In addition, low digital literacy and reliance on manual systems increase the risk of errors and reduce the quality of financial reporting. These limitations lead to low accountability, restricted access to funding, and declining stakeholder trust. The study highlights that human resources are the key determinant in the successful implementation of PAP. Recommendations include regular training, professional mentoring, the use of simple accounting applications, and institutional support from pesantren leaders, government, and professional accounting bodies. Keywords: Pesantren Accounting Guidelines, Human Resources, Accountability, Financial Reporting, Pesantren